Kesan pembelajaran sejarah melalui multiple document-based lessons (MDBL) terhadap pengetahuan sejarah dan kemahiran pemikiran sejarah - Kaviza, Manar Karam (2020)
Learning history through text analysis has positive impact on students’ understanding, literacy, interest, and engagement. However, more researches is needed to examine effectiveness for historical knowledge and thinking skills through the integration of multiple historical sources. The purpose of this study is to identify the impact of Multiple Document-Based Lessons (MDBL) on historical knowledge and historical thinking skills. Historical thinking skills have five constructs -understanding chronology, exploring evidence, interpretation, imagination, and rationalization. This study is also conducted to identify the retention effect of MDBL on historical knowledge and historical thinking skills among students. The research method is a quasi-experiment with 3X3 factorial design. The first independent variable is; the teaching method which is multiple document-based lessons (MDBL), document-based lessons (DBL), and conventional teaching method. The second independent variable is the test time which is pre-test, post-test, and extended posttest. The sample through a cluster sampling technique, involves a total of 102 Form One students from three regular secondary schools in a state in the northern Peninsular Malaysia. The research instruments have been certified by three experienced evaluators in the field of historical education and have a good reliability of scores, difficulty indices, and discrimination indices. The data were analyzed using descriptive and inferential (SPANOVA test) statistics using IBM SPSS version 24. The findings of the study show that the MDBL is more effective and significant for historical knowledge and historical thinking skills as well as the retention of both compared to DBL and conventional teaching method. Therefore, there were significant evidence to indicate that the MDBL is more effective in history education, in line with the innovation in existing historical teaching methods and the development of information technology. This study has implications on the use of the multiple sources approach, teaching pedagogy, profesional development, and digitalization of historical documents.